EARNED VALUE MANAGEMENT SYSTEM FOR EVALUATING PROJECT PERFORMANCE - Rahmana, Arief; Hartati, Verani (International Journal of Psychosocial Rehabilitation, 2020)
Project management is becoming a well-known and popular science for engineers to make project planning and controlling effective in compliance with clients’ contractual requirements. Successful projects were indicated by the achievement of meeting project requirements and specifications and being completed on schedule and within budget. To gain a successful project, an effective project control approach must be designed, developed, and implemented to provide insight into how to finish the project on time and within budget. It is believed that Earned Value Management System (EVMS) is able to control projects effectively because it integrates scope, schedule, and cost of the project. EVMS can obtain early warning and predict the outcome of projects. If our projects didn’t meet certain requirements and specifications, we will know earlier before we continue our project. The main key metrics of EVMS are planned value (PV), earned value (EV), actual cost (AC), and budgeted at completion (BAC). Finally, this paper described the concept and application of EVMS to control project performance in order to have the project completed on schedule and within budget.